Dinamika Pernikahan Lintas Agama Dalam Tafsir Al-Nukat Wa Al-'Uyun Karya Al-Mawardi - Septhiana Lutfia Hajar; Taj Zahi El Huda; Abu Bakar Yamani (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
ABSTRACT Recently, a regulation has been issued that prohibits interfaith marriages. This has sparked various comments. In addition, the number of interfaith marriages in Indonesia has been quite high since 2005. This raises the question, as Indonesia is a country with a strong belief that 'marry someone of the same religion'. Is it only used as a passing wind? So what is the law of interfaith marriage when viewed from the interpretation? Departing from this background, the author feels interested in studying this type of marriage by looking at the tafsir, namely Tafsir al-Nukat wa al-'Uyun by al-Mawardi. The focus of discussion in this study is surah al-Baqarah verse 221, al-Maidah verse 5, al-Nisa verse 24 and al-Mumtahanah verse 10. The research method applied in this research is library research with maudhui technique, which is to search for reading sources through books, articles, journals, magazines, or literature related to the theme which is then classified according to the theme. The results obtained explain that in his tafsir, al-Mawardi showed a cautious attitude in determining the law of interfaith marriage. In one condition, interfaith marriage is allowed with the provision that Muslim men marry women ahl kitab. As for Muslim women, it is forbidden to marry a polytheist man or even a man of the book. Keywords: Interfaith Marriage, al-Mawardi, Fiqh